Flight to Liquidity on the Tokyo Stock Exchange during the 2008 Share Market Crashes - Maeda, Brooke Alexandra (International Journal of Economics and Financial Issues, 2015)
This paper explores the existence of the flight-to-liquidity phenomenon for shares which are traded on the Tokyo Stock Exchange during share market crashes. Using data from the First section of the Tokyo Stock Exchange, the existence of a flight-to-liquidity during the 2008 share market crashes is clearly documented. The Tokyo Stock Exchange differs from other major exchanges as price limit rules restrict the daily price movements of shares. It provides a unique setting to test if a flight-to- liquidity occurs even when price limit rules may reduce market liquidity and delay price discovery. This study shows that despite having different trading rules, a flight-to-liquidity occurred during times of market uncertainty as investors were less willing to hold illiquid assets and rushed to sell these assets. The results are robust for smaller crash days and for different proxies of illiquidity. Keywords: Crash; Flight to liquidity; Share returns. JEL Classifications: G01; G12; G14